2021
DOI: 10.12737/2073-0462-2021-39-44
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of Clonal Micropropagation of Berry Crops

Abstract: The aim of the study is to optimize the conditions for in vitro cultivation of blue honeysuckle, raspberry and strawberry. The work was carried out in 2012-2020. The Murasige-Skuga medium (1/2 MS) was the control for all cultures for the initiation of explants. Additionally, we used a modified nutrient medium 1/2 MS with a reduced NH4 content by 15 % compared to the base MS; and Woodi Plant Medium (1/2 WPM) for honeysuckle; for raspberries - Quoirin-Lepoivre (1/2 QL) and 1/2 Anderson; for strawberries - 1/2 MS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 4 publications
0
0
0
1
Order By: Relevance
“…All experiments were conducted in the Laboratory of Plant Biotechnology at Tsitsin Main Botanical Garden of the Russian Academy of Sciences (MBG RAS), Moscow, Russia. The generally accepted methods of plant biotechnology (Butenko, 1964) developed in the Laboratory (Molkanova et al, 2018) were used in this study.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…All experiments were conducted in the Laboratory of Plant Biotechnology at Tsitsin Main Botanical Garden of the Russian Academy of Sciences (MBG RAS), Moscow, Russia. The generally accepted methods of plant biotechnology (Butenko, 1964) developed in the Laboratory (Molkanova et al, 2018) were used in this study.…”
Section: Methodsmentioning
confidence: 99%
“…Some studies showed that the determination of the morphogenetic potential of most taxa mostly depends on the genetic traits of the plants (Mitrofanova, 2018;Molkanova et al, 2018;Marino;Bertazza, 1990). The regeneration capacity of the explants of different Actinidia species varied significantly; A. arguta and A. polygama developed faster than A. kolomikta at the micropropagation stage (Figure 1), which correlated with their growth dynamics during introduction.…”
Section: Shoot Multiplicationmentioning
confidence: 98%
See 1 more Smart Citation
“…Обеспечение быстрого размножения эксплантов в течение культивирования в нескольких пассажах достигается снятием апикального доминирования при добавлении в питательную среду оптимальной концентрации цитокинина и правильным подбором питательной среды. Исследованиями, проведенными ранее [16], установлено, что оптимальной питательной средой для культивирования всех косточковых культур являлась среда Кворина-Лепорье в сравнении с Мурасиге-Скуга, Вуди Плант Медиум и Гамборга. Также выявлено, что совместное использование в последнем пассаже пролиферации 6-БАП в концентрации 0,5 мг/л, ГК -0,2 мг/л, ИМК -0,2 мг/л приводило к увеличению выхода пригодных для укоренения микрочеренков.…”
unclassified